Nanocarrier-based formulations: Regulatory Challenges, Ethical and Safety Considerations in Pharmaceuticals - Kardani, Sunil L. (Asian Journal of Pharmaceutics (AJP), 2024)
Nano-formulations represent an innovative approach in pharmaceuticals, offering enhanced drug delivery, improved therapeutic efficacy, and reduced side effects. This abstract delves into the regulatory, ethical, and safety facets associated with these formulations. Regulatory challenges form a pivotal aspect, encompassing the need for specific guidelines tailored to nano-based drugs. Addressing these challenges involves a comprehensive evaluation of characterization techniques, stability assessments, and establishing standardized protocols for manufacturing and quality control. Regulatory bodies worldwide face the task of developing adaptable frameworks to streamline approval processes, ensuring efficacy and safety while expediting the translation of research into clinical applications. Ethical considerations in nano-formulations revolve around informed consent, risk-benefit assessments, and equitable access to these advancements. Balancing the potential benefits against potential risks and ensuring transparent communication with stakeholders becomes imperative in ethical decisionmaking. Moreover, equitable distribution and affordability of these advanced therapies pose ethical dilemmas in healthcare systems globally. Safety considerations encompass a thorough understanding of nanomaterial interactions within the biological milieu, potential toxicity, and long-term effects. Robust safety assessments, including in vitro and in vivo studies, are essential to ascertain biocompatibility and mitigate unforeseen risks associated with nanocarriers. Continuous monitoring and postmarket surveillance further ensure ongoing safety evaluation. Collaborative efforts among regulatory agencies, researchers, health-care providers, and ethicists are pivotal to harness the potential of these formulations while ensuring patient safety, ethical practice, and regulatory.